2017
DOI: 10.1371/journal.pone.0188030
|View full text |Cite
|
Sign up to set email alerts
|

Drug abusers have impaired cerebral oxygenation and cognition during exercise

Abstract: BackgroundIndividuals with Substance Use Disorder (SUD) have lower baseline metabolic activity of the prefrontal cortex (PFC) associated with impairment of cognitive functions in decision-making and inhibitory control. Aerobic exercise has shown to improve PFC function and cognitive performance, however, its effects on SUD individuals remain unclear.PurposeTo verify the cognitive performance and oxygenation of the PFC during an incremental exercise in SUD individuals.MethodsFourteen individuals under SUD treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 52 publications
0
19
0
2
Order By: Relevance
“…Importantly for the purposes of the present study, Bunce et al [28] have used fNIRS imaging to show enhanced responses to alcohol cues in non-treatment-seeking alcohol-dependent patients (compared to social drinkers). In the sole study to examine craving for alcohol and cocaine, discussed in detail in the following, Grandjean da Costa et al [29] found exercise-induced increases in oxygenated blood concentrations in the prefrontal cortex compared to baseline, accompanied by lower craving scores. Increases in oxygenation were, however, less pronounced than those in healthy controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly for the purposes of the present study, Bunce et al [28] have used fNIRS imaging to show enhanced responses to alcohol cues in non-treatment-seeking alcohol-dependent patients (compared to social drinkers). In the sole study to examine craving for alcohol and cocaine, discussed in detail in the following, Grandjean da Costa et al [29] found exercise-induced increases in oxygenated blood concentrations in the prefrontal cortex compared to baseline, accompanied by lower craving scores. Increases in oxygenation were, however, less pronounced than those in healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…To date, one study has examined the effect of an acute exercise bout on cocaine and alcohol craving, and has employed fNIRS during a test of inhibitory control to examine whether this may be a moderating factor. Grandjean da Costa et al [29] reported reductions in cravings for alcohol or cocaine following a maximal exercise test; however, no significant improvements in reaction time on the Stroop test were observed. While this study is an important initial step in exploring whether, and to what extent, exercise-induced reductions in craving occur, and are moderated by inhibitory control, two aspects of the study design might obscure certain effects.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the wide range of benefits that exercise promotes on frontal regions of the brain (Hillman, Erickson, & Kramer, 2008;Tempest & Parfitt, 2016), cognition, ANS control and psychosocial aspects (Bahrke & Morgan, 1978;Flausino, Da Silva Prado, de Queiroz, Tufik, & de Mello, 2012). Studies have also suggested aerobic exercise as a possible complementary tool to treat substance use disorder such as alcohol and cocaine Grandjean da Costa et al, 2017;Manthou et al, 2016;Roessler, 2010). Despite the wide range of benefits, aerobic exercise is usually performed at low and moderate intensity during long training sessions (>30 min), becoming monotonous and only having the effects experienced after several weeks.…”
Section: Introductionmentioning
confidence: 99%
“…as taxas de mortalidade (Gebel et al, 2015). (Blumenthal et al, 1999;Blumenthal et al, 2007;Abrantes et al, 2017;Gerber et al, 2016;Blumenthal & Doraiswamy, 2014;Berhman et al, 2014;Adamoli & Azevedo, 2009); para o tratamento da ansiedade (Stubbs et al, 2017;Khanzada et al, 2015;Björg Helgadóttir et al, 2015;); nos comportamentos aditivos (Brown et al, 2010;Grandjean da Costa et al, 2017); no transtorno afetivo bipolar (Wright K et al, 2012;MacQueen & Memedovich, 2017;Proudfoot et al, 2012) e no transtorno de estresse pós traumático (TEPT), onde os sintomas pós-traumáticos, e depressivos, melhoraram, significativamente (Shivakumar et al, (2017). A maioria dessas condições são frequentes em portadores de TJ (Tavares et al, 2003).…”
Section: Exercício Físico E Saúde Mentalunclassified
“…Contudo, não foram observadas diferenças significativas entre os grupos para as variáveis de jogo. (Brown et al, 2010;Grandjean da Costa et al, 2017).…”
Section: Efeitos Do Exercício Físico Nas Variáveis De Jogounclassified